Requests for repeat medication prescriptions and frequency of acute episodes in asthma patients. - Osman, L; Friend, J; Legge, J; Douglas, J (1999)
This study was conducted to determine if suboptimal use of inhaled steroid and over-reliance on bronchodilator medication to control asthma symptoms is associated with higher risk of acute asthma episodes. Details of repeat prescriptions for medication and use of health services over 12 months were collected for 754 adult outpatients with asthma; all were prescribed inhaled corticosteroid. Patients who requested less than five prescriptions per year were considered suboptimal users. Patients who requested seven or more bronchodilator prescriptions and less than five inhaled steroid prescriptions had significantly more family physician consultations for asthma episodes (p < 0.05), more hospital admissions (p < 0.05), and more disturbed nights in the week before hospital or family physician review (p < 0.05). Some patients with more severe asthma put themselves at risk by relying on bronchodilator medication rather than regular inhaled steroid for asthma control. Among patients who were low bronchodilator users, those who requested few inhaled steroid prescriptions were younger and more anxious but did not have an increased risk of acute asthma episodes.